2021
DOI: 10.1038/s41467-021-23254-1
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM reveals the architecture of placental malaria VAR2CSA and provides molecular insight into chondroitin sulfate binding

Abstract: Placental malaria can have severe consequences for both mother and child and effective vaccines are lacking. Parasite-infected red blood cells sequester in the placenta through interaction between parasite-expressed protein VAR2CSA and the glycosaminoglycan chondroitin sulfate A (CS) abundantly present in the intervillous space. Here, we report cryo-EM structures of the VAR2CSA ectodomain at up to 3.1 Å resolution revealing an overall V-shaped architecture and a complex domain organization. Notably, the surfac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 56 publications
1
38
0
Order By: Relevance
“…The conformation in the former work 10 is different from ours, which might be due to the fact that VAR2CSA proteins in apo structure and complex structure are from two different P. falciparum strains. In the other study 11 , FCR3 VAR2CSA shared a sequence identity of 79% with 3D7 VAR2CSA used in our study, but no ligand density was reported in their complex structure. Most importantly, beyond the structural study, we also generated VAR2CSA fragments and 9-site mutations, and evaluated their binding activity to either isolated CSA or placental and tumor cell lines.…”
mentioning
confidence: 42%
See 2 more Smart Citations
“…The conformation in the former work 10 is different from ours, which might be due to the fact that VAR2CSA proteins in apo structure and complex structure are from two different P. falciparum strains. In the other study 11 , FCR3 VAR2CSA shared a sequence identity of 79% with 3D7 VAR2CSA used in our study, but no ligand density was reported in their complex structure. Most importantly, beyond the structural study, we also generated VAR2CSA fragments and 9-site mutations, and evaluated their binding activity to either isolated CSA or placental and tumor cell lines.…”
mentioning
confidence: 42%
“…Recently, the cryo-EM structures of the VAR2CSA ectodomain from P. falciparum strain FCR3 and VAR2CSA ectodomain from P. falciparum strain NF54 complexed with CSA were reported 10 . Meanwhile, another study also revealed the cryo-EM structures of the VAR2CSA ectodomain from P. falciparum strain FCR3 and its complex with placental chondroitin sulfate 11 . Uniquely, our structural study showed that CSA binding induced significant conformational changes to secure ligand binding, which was not reported by these two works 10 , 11 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term childhood exposure to the parasites can result in the development of protective antibodies; however, first-time pregnant mothers become susceptible again ( Teo et al, 2016 ). Their susceptibility can be attributed to the P. falciparum erythrocyte membrane protein-1 (PfEMP1), a major variant surface antigen displayed on the surface of P. falciparum -infected erythrocytes (IEs) that serves as an adhesin ( Lennartz et al, 2019 ; Wang et al, 2021 ). Each parasite has up to 60 var genes that encode the PfEMP1 molecules, and only a single variant is expressed at any one time ( Smith et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of polysaccharide chains containing hydrophilic functional groups including hydroxyl, amino, and carboxyl groups can enhance solubility of the new conjugates. Compared to synthetic polymers, polysaccharides frequently act as biological recognition elements (Kim et al, 2020;Wang et al, 2021), and may be bioactive (Bauer, Jin, Zhang, & Linhardt, 2021;Griffin, Sorum, Miller, Goddard 3rd, & Hsieh-Wilson, 2021;Kwon et al, 2020;La Gatta et al, 2020;Shelke, James, Laurencin, & Kumbar, 2014;Stopschinski et al, 2018). Many polysaccharides, such as cellulose and some of its derivatives, are in approved pharmaceutical formulations, and/or on the FDA Generally Recognized as Safe (GRAS) list.…”
Section: Introductionmentioning
confidence: 99%